Studies on in vitro Antibacterial, Antifungal Property and Antioxidant Potency of Murraya paniculata - Sundaram, Mohana; Sivakumar; Karthikeyan; Bhuvaneshwari; Aishwarya; Thirumalai; Pennarasi (Pakistan Journal of Nutrition, 2011)
In this investigation, Murraya paniculata was analyzed for its antibacterial, antifungal and antioxidant properties. The antibacterial property of Murraya paniculata was studied against different bacteria include Escherichia coli, Proteus mirabilis, Salmonella typhi, Enterobacter aerogenes and Shigella flexineri and showed growth inhibition activity at concentrations ranging of 300-500 mg. The antifungal property of aqueous, ethanol and hexane extracts of Murraya paniculata was studied by agar well diffusion method and we observed that only at 500 mg, it showed positive inhibitory effect. The antioxidant effect of those extracts was also studied against α-tocopherol as a control. From the results, Ethanol extract at the concentration of 500 μg/ml showed 67.77% antioxidant activity against 500 μg/ml of α-tocopherol which showed 72.24% as a standard reference.